Teacher deployment of 'oh' in known-answer question sequences. Issue 1 (2nd January 2016) - Hosoda, Yuri
Abstract : This conversation analytic study describes some specific interactional contexts in which native English-speaking teachers produce 'oh' in known-answer question sequences in English language classes. The data for this study come from 10 video-recorded Japanese primary school English language class sessions. The analysis identified three specific interactional contexts in which teachers deploy the particle in receipting students' answers to known-answer questions: (a) when they reinforce positive assessments, (b) when they act out dialogues with students and (c) when they respond to students' 'unexpected' answers to their questions. Through the exploration of the teachers' deployment of 'oh' in third positions, this study uncovers teachers' on-line attention to both local interactional contexts and overall pedagogical objectives. In addition, this study discusses how teachers' deliberate or incidental deployment of 'oh' in third positions potentially enhances student opportunities for learning.